Is there a pot of gold at the end of the rainboow for Asian low cost airlines - Yap, Jeffrey Peng Poh (2006)
This market study will seek to understand the impact of the Low Cost Carriers (LCC) model in Asia. There are generally two LCC business models, Value-Based or Deep Discount model. Between the two basic low cost business models is a third variant - the Long-Haul Discount model. Asia Pacific, a far-flung region and accounts for 56% of the world population and favorable macro environments coupled with a large growing affluent population will fuel new demand for discretionary travel. Asian LCC with the right business model and strategies will definitely ride on this huge potential and emulate the success demonstrate in North American and Europe. The current LCC market share is estimated to be about 5% in Asia Pacific and could increase to about 11% in 2010, and could reach higher rates if external macro environment remains favorable. Although the pace of bilateral liberalization is spreading at a much slower pace than in other markets around the world, the emergence of low cost carriers in Asia Pacific is accelerating this trend. This market trend will greatly benefit the aerospace industry suppliers, aircraft lessors and OEM such as Hamilton Sundstrand (HS). HS engineering expertise and capabilities in integrating their whole supply chain to bring added value to their customers has put them in a strong position and a source of their competitive advantage.